Improving the Learning Outcomes of Class IV Natural and Social Science Students on Knowing Maps Through the Problem Based Learning Model - Umami, Faridatul; Rimadoni, Etika Utami Lutfi (MANDAILING GLOBAL EDUKASIA, 2024)
The teaching of IPAS (Integrated Science and Social Studies), particularly in the topic of map recognition, often still relies on traditional methods that are less effective in enhancing student learning outcomes. Problem-Based Learning (PBL) offers a more engaging and effective alternative by encouraging active student participation and deeper conceptual understanding through real-world problem-solving. This study aims to improve fourth-grade students' understanding of maps specifically, their knowledge of what maps are and how to read them by implementing the PBL model. The research was conducted using a classroom action research approach. In the pre-cycle, the average student score was 71.15, with only 34.61% (9 students) achieving a score of 75 or higher. After the first cycle, the average increased to 77.5, with 50% (13 students) meeting or exceeding the benchmark. In the second cycle, the average score rose significantly to 93.65, with 96.15% (25 students) scoring above 75. These findings indicate that the use of PBL, supported by map-based learning media and PowerPoint presentations, significantly improves student learning outcomes in the topic of map recognition.